Erratum to: “Piecewise Loglinear Estimation of Efficient Production Surfaces” - Banker, Rajiv D.; Maindiratta, Ajay (Management Science, 1986)
Erratum to: “Piecewise Loglinear Estimation of Efficient Production Surfaces”, Management Sci. 32 (1, January) (1986) 126–135.